Urinary Markers in the Everyday Diagnosis of Bladder Cancer. Issue 4 (October 2013) - Dal Moro, Fabrizio; Valotto, Claudio; Guttilla, Andrea; Zattoni, Filiberto
Bladder cancer (BC) represents the fourth most common neoplasia in men and the ninth most common cancer in women, with a significant morbidity and mortality. Cystoscopy and voided urine cytology (involving the examination of cells in voided urine to detect the presence of cancerous cells) are currently the routine initial investigations in patients with hematuria or other symptoms suggestive of BC. Around 75-85% of the patients are diagnosed as having non-muscle-invasive bladder cancer (NMIBC). Despite the treatment, these patients have a probability of recurrence at 5 years ranging from 50 to 70% and of progression to muscle invasive disease of 10-15%. Patients with NMIBC must undergo life-long surveillance, consisting of serial cystoscopies, possibly urine cytology and ultraso-nography. Cystoscopy is unsuitable for screening because of its invasiveness and costs; serial cystoscopies may cause discomfort and distress to patients. Furthermore, cystoscopy may be inconclusive, falsely positive or negative. Although urine cytology has a reasonable sensitivity for the detection of high-grade BC, it lacks sensitivity to detect low-grade tumors (sensitivity ranging from 4 to 31%). The overall sensitivity and specificity of urine cytology range from 7 to 100 and from 30 to 70%, respectively. There is a need for new urine biomarkers that may help in BC diagnosis and surveillance. A lot of urinary biomarkers with high sensitivity and/or specificity have been investigated. Although none of these markers have proven to be powerful enough to replace standard cystoscopy, some of them may represent accurate predictors of BC. A review of recent studies is presented.